High-quality textured SnSe thin films for self-powered, rapid-response photothermoelectric application. (June 2020) - Zhong, Yujia; Zhang, Li; Linseis, Vincent; Qin, Bingchao; Chen, Wenduo; Zhao, Li-Dong; Zhu, Hongwei
Abstract: Tin selenide (SnSe) has attracted great attention in thermoelectrics (TE) thanks to its record high figure of merit ( ZT ) discovered in single crystal (SC). However, the practical application of SnSe SC is limited due to its extreme growth condition. With the development of flexible integrated electronics, using flexible polycrystalline TE films to substitute rigid SC becomes a main trend. Nevertheless, large resistances of TE films restrict their application as power devices. Here, self-powered SnSe-based photothermoelectric (PTE) detectors are demonstrated. The PTE detectors are sensitive to wide-spectrum and exhibit higher responsivity and respnse speed comparing with SC, due to the small heating volume, small conductive heat flux and large dissipation content of thin films. High-quality (400)-textured SnSe polycrystalline thin films are one-step synthesized by chemical vapor deposition. In-situ in-plane TE measurement shows that the obtained SnSe films possess a dimensionless ZT of 0.15 and a power factor of 0.322 mW m −1 K −2 at 550 K, showing SC level TE performance at low temperatures. Graphical abstract: SnSe thin films with strong (400) texture are prepared by one-step chemical vapor deposition, showing single crystal level in-plane thermoelectric performance. Self-powered SnSe thin film-based photothermoelectric detectors are demonstrated. Image 1 Highlights: High-quality (400)-textured SnSe polycrystalline thin films are prepared by chemical vapor deposition. The SnSe films possess a dimensionless ZT of 0.15 and power factor of 0.322 mW m −1 K −2 at 550 K. Self-powered SnSe-based photothermoelectric detectors are demonstrated. The detectors exhibit higher responsivity and speed comparing with single crystal.